INTERRELATION BETWEEN COMORBIDITY AND MORTALITY RATES IN ELDER PATIENTS WITH POLYTRAUMAS - M. L. Mukhanov; A. N. Blazhenko; A. V. Shevchenko; A. K. Shkhalakhov; R. G. Oleynikov (Инновационная медицина Кубани)
Regarding world wide tendency to population ageing, active life style of the elderly leads to growing various traumas, including severe concomitant injuries. Comorbidity does not only complicate diagnosis process and treatment in non-advanced medical centres, but in cases with concomitant injuries may result in unexpected decompensation of patient condition, down to unfavourable treatment results. Thus, coexisting somatic pathology is a serious challenge for the public health system as several accompanying diseases exacerbate management and diagnosis procedures.Objective. Value influence of accompanying pathology on probable lethal outcome in elder patients with polytraumas.Material and Methods. We analysed cases of elder patients with polytraumas (n = 163). To standardise studies and compare them properly we used Charlson comorbidity index.Results. Accompanying somatic pathology influences outcomes in patients with severe combined traumas: Charlson index >5, in patients older 60 years it’s prognostically unfavourable for life, irrespective of trauma severance.Conclusion. Application of comorbidity index allows to object life prognosis and possibility of surgical stage performance in elder patients with polytraumas regarding the concept of injury dynamic control.